Attitudes towards seeking mental health counselling among cancer patients with the symptom of depression, anxiety, and stress - Wong, Wing Hoe; Mohd Noah, Sidek (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This study envisioned to examine the psychological help seeking attitudes in terms of seeking mental health counselling among cancer patients with the symptom of depression, anxiety, and stress. This study was conducted on 240 cancer patients involving 120 male and 120 female patients from the Department of Radiotherapy and Oncology, Hospital Kuala Lumpur. The Depression, Anxiety, and Stress Scale (DASS) and the Attitudes Toward Seeking Professional Psychological Help Scale (ATSPPHS) were used in the study as instruments for data collection. The data were analysed using mean, frequency, and percentage. The data were also analysed using Pearson correlation. The raw scores collected from the administration of the DASS were analysed to depict the state of psychological wellbeing of the patients in relation to the prevalence of symptom of depression, anxiety, and stress. The raw scores obtained from the ATSPPHS were used to describe the extend of cancer patients would seek mental health counselling. The interceding influence of attitudes toward seeking mental health counselling between prevalence of psychological distress and intent to seek mental health counselling was examined through correlational studies. Findings show that attitudes toward seeking mental health counselling have significant negative correlation with all dependent variables of symptom of psychological distress – depression, anxiety, and stress. Implications of the research and suggestions for further research were also discussed.